Proposta de metodologia híbrida para determinação de capacidade de hospedagem de fontes de geração distribuída com fonte solar em redes de distribuição - Lima, Ezequiel Junio de (2021)
The concept of hosting capacity (HC) is becoming more widespread, as it is an approach of ample scope and brings with it an understanding into the impacts of distributed generation on grids. Various methods for calculating HC have been developed over recent years and are classified as deterministic, stochastic and time series, each with its respective pros and cons. Within this context, the author of the present thesis proposes a hybrid methodology that combines the deterministic and time series methods into the HC calculation of a real feeder, located in Poços de Caldas, MG, from the energy utility DMED. The feeder referred to herein was modelled and analyzed, while taking into consideration variations in loads and power injected by distributed generation (DG) sources on different buses that make up the system. Finally, the results obtained demonstrate the efficiency of the proposed method.